Introducing an Integrated Model of Talent Development: From Research to Practice. Issue 2 (3rd April 2023) - Mills, Andrew; Butt, Joanne; Maynard, Ian
Abstract: In this paper we are introducing an Integrated Model of Talent Development (IMTD). Predicated on a line of research that originally focused on elite youth soccer (cf. Mills et al., 2012 ; Mills et al., 2014a, b ), the IMTD is a research-informed model that elucidates the interplay between environmental and psychological factors in the effective development of athletic potential. We introduce the core components of the model including environment strengths (e.g., involvement, opportunity, challenge) and development strengths (e.g., perseverance, self-determination, adaptability), and highlight how these interact in multiplicative ways to positively shape athletic potential along the developmental pathway. An example of how the model can be used in practice is included.